Cationic Conjugated Polyelectrolytes with Aggregation‐Induced Ratiometric Fluorescence. Issue 18 (16th March 2022) - Mei, Li‐Jun; Li, Chong; Zhao, Peng‐Ju; Chen, Tao; Tian, Rui; Guo, Jing; Zhu, Ming‐Qiang
Abstract: The molecular diversity of aggregation‐induced emission remains a challenge due to the limitation of conventional synthesis methods. Here, a series of novel neutral and cationic conjugated polymers composed of various ratios of tetraarylethylene (TAE) containing a bridged oxygen (O) and fluorene (F) units is designed and synthesized via the geminal cross‐coupling (GCC) of 1, 1‐dibromoolefins. The incorporation of TAE segments into the conjugated backbone of polyfluorene produces pronounced aggregation‐induced ratiometric fluorescence, i.e., aggregation‐induced emission (AIE) at 520–600 nm and grows synergistically with aggregations‐caused quenching (ACQ) at 400–450 nm. The content of fluorene unit in the polymer backbones determines the intensity of the initial fluorescence in the blue light region. The huge distinction (about 150 nm) in dual emission wavelengths caused by the environment change makes these conjugated polyelectrolytes particularly suitable for ratiometric fluorescence sensing. Based on electrostatic interaction mechanism, the gradual addition of heparin into the cationic conjugated polymers aqueous solutions can induce dual‐color fluorescence changes with a detection limit of 9 × 10 −9 m . This work exhibits the great facility of using GCC reaction to synthesis the conjugated TAE polymers with superior AIE properties and special functions. Abstract : A series of novel cationic conjugated polyelectrolytes POa F1+b + containing tetraarylethylene and fluorene are constructed by geminal cross‐coupling reaction. They show high‐contrast dual‐color ratiometric fluorescence response to physical environment change and have been used as fluorescence sensors for heparin detection with a high detection limit of 9 × 10 −9 m and a high selectivity.